In-season strength and power training considerations for professional soccer teams competing within national level competitions - Wing, C. (Strength and Conditioning Journal, 2018)
Strength and power have been widely reported as essential qualities to successful soccer performance. However, improving these qualities within the in-season period seems to provide significant challenges. These include a chaotic fixture schedule, increased levels of fatigue, and issues surrounding concurrent training. A variety of methods may be used by strength and conditioning (s&c) coaches to overcome these. This may include adopting a nonlinear periodization plan and the careful manipulation of the variables within it. At all times, the s&c coach should be flexible and able to easily adjust programming to the changing competitive schedule.